Effects of SP600125 on Proliferation and Invasion of Human Cervical Cancer HeLa Cells - MO Yanxiu; YAO Feihong; LIU Juntong; HU Ziang; LI Mulan (Zhongliu Fangzhi Yanjiu, 2022)
Objective To investigate the effect of SP600125 on the proliferation, cell cycle, apoptosis and invasion of human cervical cancer HeLa cells. Methods CCK-8 method was used to detect the proliferation of HeLa cells treated with different concentrations of SP600125 at different time points. The 20 μmol/L of SP600125 was determined for subsequent experiments. Cell proliferation ability was detected using plate clone formation assay; nuclear morphology was observed by DAPI staining; cell cycle and apoptosis were measured by flow cytometry; cell migration and invasion were detected by cell scratch and Transwell methods; the mRNA and protein levels of p53, Mad2L1 and CDC20 were measured by qRT-PCR and Western blot after SP600125 treatment at different time points. Results Compared with control group (0.1%DMSO), cells proliferative activity were reduced by 10, 20, 30, 40 and 50 μmol/L SP600125 treatment for 24h. Compared with control group, the rate of apoptosis was significantly increased in SP600125 treatment groups, and the cell proportion in G2/M phase increased (P < 0.001), while the cell proportion in G0/G1 phases cells was reduced after SP600125 treatment for 24h and 48h (P < 0.001), and the clonal number, migration and invasion ability of HeLa cells also decreased significantly (P < 0.001). qRT-PCR and Western blot results showed a significant decrease in Mad2L1 mRNA and protein expression (P < 0.05) and a significant increase in p53 and CDC20 mRNA and protein expression (P < 0.01). Conclusion SP600125 can induce cell cycle arrest of cervical cancer HeLa cells in G2/M phase by upregulating p53 and CDC20 and downregulating Mad2L1 expression, and promote cell apoptosis to inhibit cell proliferation, migration and invasion.